Plasma (Global Journal of Science Frontier Research, 2020)
How did the Superforce come into play The answer lies in the plasma In this paper we consider the plasma and well-established equations By these equations we see that the plasma fits well into the theory of Astrotheology
Keywords: plasma; astrtothehogy